The voice of iwi radio : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Business Studies at Massey University - Allan, Grant (Massey University, 1998)
The author presents findings from a project examining the state of indigenous radio in New Zealand. Interviews with 15 Maori radio station managers were conducted for the purpose of identifying and examining the difficulties stations are presently experiencing. Interviews were also conducted with noted commentators and government agency staff to clarify concerns and identify avenues to overcome difficulties. Results from interviews, including themes generated through a thematic content analysis of participant's responses, are provided. The study has unearthed a number of significant findings. Specifically, the research points to difficulties with funding, staffing and training. While radio stations on the whole were able to fulfil contractual obligations to Te Mangai Paho, limitations with infrastructure have hindered their development. The thesis provides recommendations and identifies further areas of inquiry.
Keywords: Radio broadcasting, New Zealand; Maori radio; Ethnic radio broadcasting; Broadcasting policy, New Zealand